Enterprise Architecture Design of Tourism Supply Chain Management Platform Application at the Level of Business Process Flow and Information - Suhana Minah Jaya; Andri Hermawan (Jurnal Toursci, 2026)
Background. The tourism sector in Indonesia plays a strategic role in national economic growth; however, its performance is constrained by fragmented supply chains, lack of integration among stakeholders, and the absence of a unified digital platform. Aims. This study aims to design an Enterprise Architecture (EA) for a Tourism Supply Chain Management (TSCM) digital platform that integrates tourism actors from upstream to downstream. Methods. The research adopts a qualitative design approach, utilizing Focus Group Discussions (FGD) involving 110 participants representing tourism associations, service providers, local governments, and tourists. Result. The findings reveal critical issues related to distribution inefficiencies, price instability, service quality inconsistency, and supply uncertainty. Based on stakeholder needs analysis, the study develops an enterprise architecture blueprint comprising a Business Model Canvas, application service process flow, service network design, organizational structure, and graphical user interface (GUI). Conclusion. The proposed architecture provides a comprehensive framework for coordinating information, distribution processes, and payment systems within the tourism supply chain. Implementation. This research contributes a structured EA-based solution that supports efficiency, price stability, and service quality enhancement in Indonesia’s tourism industry.